Effects of calcium hydroxide addition on the physical and chemical properties of a calcium silicate-based sealer - KUGA, Milton Carlos (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2014)
Recently, various calcium silicate-based sealers have been introduced for use in root canal filling. The MTA Fillapex is one of these sealers, but some of its physicochemical properties are not in accordance with the ISO requirements. OBJECTIVE: The aim of this study was to evaluate the flowability, pH level and calcium release of pure MTA Fillapex (MTAF) or containing 5% (MTAF5) or 10% (MTAF10) calcium hydroxide (CH), in weight, in comparison with AH Plus sealer. MATERIAL AND METHODS: The flowability test was performed according to the ISO 6876:2001 requirements. For the pH level and calcium ion release analyses, the sealers were placed individually (n=10) in plastic tubes and immersed in deionized water. After 24 hours, 7 and 14 days, the water in which each specimen had been immersed was evaluated to determine the pH level changes and calcium released. Flowability, pH level and calcium release data were analyzed statistically by the ANOVA test (α=5%). RESULTS: In relation to flowability: MTAF>AH Plus>MTAF5>MTAF10. In relation to the pH level, for 24 h: MTAF5=MTAF10=MTAF>AH Plus; for 7 and 14 days: MTAF5=MTAF10>MTAF>AH Plus. For the calcium release, for all periods: MTAF>MTAF5=MTAF10>AH Plus. CONCLUSIONS: The addition of 5% CH to the MTA Fillapex (in weight) is an alternative to reduce the high flowability presented by the sealer, without interfering in its alkalization potential.